2018
DOI: 10.1177/2153368718754638
|View full text |Cite
|
Sign up to set email alerts
|

“We All Have Stories”: Black Muslim Immigrants’ Experience With the Police

Abstract: Understanding the relationships between immigrants and refugees and the police is a critical research task with implications for both community–police partnerships and the effectiveness of law enforcement efforts. This study contributes to such an understanding by examining perceptions of police and police interactions among Somali immigrants and refugees (both first and second generation) in three communities in the United States and Canada. This article presents in-depth analyses of qualitative interview dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
(31 reference statements)
1
18
0
Order By: Relevance
“…Furthermore, Chermak et al's (2006) as well as Kochel's (2019) findings are supported: people in the respective peer group that suffered most in the event are more severely affected by the effect of police misconduct on trust and/or legitimacy. So far, this 'peer group effect' has mainly been observed among ethnic groups (Ellis et al, 2018). Depending on the type of incident, other interaction effects are also conceivable, such as social class or political ideology (Intravia et al, 2020).…”
Section: Interpretation and Discussion In The Context Of Existing Resmentioning
confidence: 98%
“…Furthermore, Chermak et al's (2006) as well as Kochel's (2019) findings are supported: people in the respective peer group that suffered most in the event are more severely affected by the effect of police misconduct on trust and/or legitimacy. So far, this 'peer group effect' has mainly been observed among ethnic groups (Ellis et al, 2018). Depending on the type of incident, other interaction effects are also conceivable, such as social class or political ideology (Intravia et al, 2020).…”
Section: Interpretation and Discussion In The Context Of Existing Resmentioning
confidence: 98%
“…Our participants also readily identified Somali culture and religion as a strength and asset, suggesting that there could be considerable pride and enthusiasm for gang prevention efforts that built on, and reinforced, these inherent strengths and values. Our past work found that although Somali community-law enforcement relations are frequently perceived as aversive, there nonetheless are examples of positive policing with this community (Ellis et al, 2020).…”
Section: Implications For Prevention and Interventionmentioning
confidence: 89%
“…Isolation stressors involve challenges related to alienation, loneliness and discrimination. Experiences of isolation, explicit and implicit bias, and discrimination are tragically common for newly arrived children (Alegria et al, 2010; Davis et al, 2021; Ellis et al, 2018). Newly arrived children may experience feelings of loneliness due to loss or lack of social support, which may be compounded by discrimination or harassment from peers, adults, or law enforcement (Ellis et al, 2014; Tienda & Haskins, 2011).…”
Section: How Can School Nurses Effectively Apply the Ricst To Our Illustration Case “Jasiel”?mentioning
confidence: 99%